A Handbook for the Teaching and Learning of Sociocultural Content with a CLIL Approach - Gil Felipe, Liana (Universidad Central "Marta Abreu" de Las Villas, 2017)
In a world where wars and ethnic and religious conflicts are abundant, peace and cultural understanding should become topics to be embraced by educational systems. This major paper presents a handbook for the teaching and learning of sociocultural content with a Content and Language Integrated Learning (CLIL) approach, aimed at evaluating the importance of learning about the society and culture of Canada and Cuba, in order to behave appropriately in the process of communication and develop understanding and respect for the foreign culture and pride towards the students´ own culture. The development of this material was attained inductively applying the following methods: historical- logical, inductive- deductive, transit from the abstract to the concrete, the systemic approach, the analytic-synthetic, participant observation, survey to the students, document analysis, and analysis of the students´ outcomes, teacher´s diary, pedagogical test, teacher reflections and interview to teachers.

Dans un monde où la guerre et les conflits ethniques et religieux sont abondants, la paix et la compréhension culturelle devront devenir sujets pour être considéré par les systèmes pédagogiques. Cette recherche présente un manuel pour l'enseignement et apprentissage des contenus socioculturels avec une approche CLIL. Son objectif principal est évaluer l´importance d´apprendre sur la société et culture du Canada et Cuba, afin de se comporter correctement dans le processus de communication et de développer la compréhension et le respect pour les cultures étrangères et la fierté pour la culture autochtone des étudiants. Le développement de la présente recherche a été accomplie de manière inductive en utilisant des méthodes suivantes: historique - logique, inductif - déductif, le passe de l´ abstract au concrète, l'approche systémique, la méthode analytique-synthétique, l´observation participante, l´ enquête aux étudiants, l´analyse des documents, l´analyse des résultats des étudiants, le journal du professeur, l´épreuve pédagogique, les réflexions du professeur et l´entretien aux professeures.
Keywords: Proceso de enseñanza-aprendizaje; Inglés; Contenido sociocultural